Enseigner l’histoire à distance en contexte d’urgence pandémique : étude des pratiques déclarées des enseignants du secondaire au Québec - Jadoulle, Jean-Louis (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
Thirty-one teachers responded to an online questionnaire about their distance teaching practices between March 2020 and June 2021. We wanted to identify their level of integration of information and communication technologies (ICT), their motivation to teach at distance, and the determinants of their pedagogical choices. The circumstances led most of them to become familiar with ICT, to explore its basic functions and, to a lesser extent, to appropriate more complex ones. The analyses suggest the existence of two groups, with a major discriminating element concerning the representation of history teaching.